POWER DISTANCE, UNCERTAINTY AVOIDANCE AND COMMITMENT TO CHANGE - Wustari Mangundjaya; Imo Gandakusuma; Mira Sekar Arumi (Jurnal Scientia, 2023)
This study aims to identify the relationship between power distance, uncertainty avoidance, and commitment to change, using the GLOBE’s and Hofstede concepts. There were 328 overall respondents, consisting of private manufacturing company employees and state-owned companies’ employees, with every 164 respondents. Research results are based on two studies for which data were collected using three scale inventories, namely Commitment to Change, Power Distance, and Uncertainty Avoidance. Descriptive and correlations techniques were used to analyse the data. Results showed that power distance and uncertainty avoidance were significantly negatively correlated with a commitment to change. In other words, people with moderate to high power distance and moderate to high uncertainty will tend to have a low commitment to change. This study’s implications can be used by management to prepare for organizational change, particularly to identify work-related values that exist in their organizations, to anticipate employees’ reactions to change. Keywords: Commitment to Change, Power Distance, Uncertainty Avoidance.